THE ETHNOBOTANY OF DUSUN PEOPLE IN TIKOLOD VILLAGE, TAMBUNAN DISTRICT, SABAH, MALAYSIA - Julius Kulip (Reinwardtia, 2014)
The ethnobotanical studies of the Dusun people in Tikolod village, Tambunan district, Sabah, Malaysia were conducted from July 25th to 30th, 2011 and from March 9th to 10th, 2012. The result shows that there were 160 species in 62 families of plants used. Among them, there were 83 species (in 36 families) of edible plants, 75 species (in 44 families) were medicines, 12 species (in nine families) were used for constructions and handicraft and eight species (in six families) were used for musical instruments and animal traps. There were 24 species of plants that have two or more uses. Of the total, 87 species or 54% were native or collected from the natural forest nearby and 73 species or 45% of these plants were exotic (introduced plants). The most commonly used of plant families were Poaceae (Gramineae) with 14 species, followed by Moraceae and Zingiberaceae, with eight species each and Arecaceae (Palmae), Cucurbitaceae, Euphorbiaceae, Rutaceae and Solanaceae, with seven species each.